2015
DOI: 10.4049/jimmunol.1402699
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory and Helper Follicular T Cells and Antibody Avidity to Simian Immunodeficiency Virus Glycoprotein 120

Abstract: T follicular regulatory cells (TFR) are a suppressive CD4+ T cell subset that migrates to germinal centers (GC) during antigen presentation by up-regulating the chemokine receptor CXCR5. In the GC, TFR control T follicular helper cells (TFH) expansion and modulate the development of high-affinity antigen specific responses. Here we identified and characterized TFR as CXCR5+ CCR7−-“follicular” T regulatory cells (TREG) in lymphoid tissues of healthy rhesus macaques, and we studied their dynamic throughout infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 66 publications
1
50
0
Order By: Relevance
“…The frequency of Tfr cells within total LN CD4 + T cells does not appear to be increased during chronic SIV282, 283 or HIV‐1 infection,284 although the absolute number of Tfr cells is increased. One report suggests that the Tfr cell frequency in the spleen may be increased during HIV‐1 infection, however 285.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 92%
“…The frequency of Tfr cells within total LN CD4 + T cells does not appear to be increased during chronic SIV282, 283 or HIV‐1 infection,284 although the absolute number of Tfr cells is increased. One report suggests that the Tfr cell frequency in the spleen may be increased during HIV‐1 infection, however 285.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 92%
“…T follicular regulatory cells (T FR ) are a subset of follicular cells that directly regulate numbers and function of T FH during HIV and SIV infection [3134]. Two studies linked relative decreases of T FR to expansions of T FH in the SIV-infected rhesus macaque model [31, 32]. Increased cell survival may contribute to the persistence of T FH as well.…”
Section: Role Of Tfh In Hiv Replication In Untreated Diseasementioning
confidence: 99%
“…Although several studies have phenotypically and functionally characterized the total population of macaque T FH cells in naïve and SIV-infected animals (23, 27-31), quantification of vaccine-induced SIV-specific IL-21-producing macaque T FH cells has not yet been reported. In order to better understand the development of humoral immune responses and the contribution of T FH to protective efficacy, in the present study we have identified and quantified SIV-specific LN-resident IL-21 + T FH cells for the first time in a pre-clinical non-human primate vaccine trial.…”
Section: Introductionmentioning
confidence: 99%